Statistical analysis of self-similar behaviour in the shear induced melting model - Lyashenko, I.A.; Borysiuk, V.N.; Manko, N.N. (Condensed Matter Physics, 2014)
The analysis of the system behavior under the effect of the additive noises has been done using a simple model of shear melting. The situation with low intensity of the order parameter noise has been investigated in detail, and time dependence of the order parameter has been calculated. A distinctive feature of the obtained dependence is power-law distribution and self-similarity. The generalized Hurst exponent of the time series has been found within multifractal detrended fluctuation analysis. It is shown that the self-similarity of the time series increases when the noise intensity reduces.